Effect of education based on health belief model on the social capital and quality of life among male teachers - Rahmatolah Dadvar; Mohammad Hossein Baghianimoghadam; Seyyed Saeed Mazloomi Mahmoodabad (Gonabad University of Medical Sciences, 2019)
This article is an experimental analysis of the relationship between social capital and quality of life based on the Health Belief Model. The research followed an experimental method. 100 male teachers were selected randomly and assigned to two groups of experimental and control (n=50 each). The instruction was conducted in nine two-hour sessions in the form of pamphlets, lectures, and group discussions and the posttest was performed after 3 months. Data were collected using three questionnaires. The comparison of the pretest and posttest mean scores in terms of the components of the health belief model, social capital, and life quality in both experimental and control groups showed that there was no significant difference between the two groups in the pretest; however, the comparison of the results in posttest showed a significant difference. Leven test calculation, T, and covariance confirmed these differences and reflected the impact of intervention and implementation of the training program on the experimental group. The results of the analysis indicate that the models applied are significant, which confirms the examined propositions. Higher levels of social capital imply greater levels of quality of life at school.